Isolation and Identification of Naphthalene Degrading Microbe from Petroleum Contaminated Soil - Bhawana Prajapati; G. Shiv; S. Gaherwal; Kiran Billore; R. Soni (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Naphthalene is a simplest Polycyclic Aromatic Hydrocarbon (PAH). PAHs are major contaminants of environment, associated with common anthropogenic activities such as oil refineries and incomplete combustion of fossil fuels. PAHs are toxic, mutagenic and carcinogenic. In the present study, bacterial strain was isolated from oil-spilled sediments were selected due to their capacity of growth in the presence of naphthalene as sole carbon and energy source. The isolates were identified by biochemical tests. Through this strain degradation of naphthalene were done. The strain belonged to Bacillus subtilis. Our results showed that the average degradation rates of naphthalene by Bacillus subtilis were recorded maximum in sample 3. According to ability of Bacillus subtilis in the degradation of naphthalene, it is recommended to use these species for remediation of oil compounds in contaminated sites.